2021
DOI: 10.1007/s40194-021-01136-w
|View full text |Cite
|
Sign up to set email alerts
|

Advances in friction stir welding by separate control of shoulder and probe

Abstract: Friction stir welding (FSW) has developed into a reliable and increasing used industrial joining technology. Various tool configurations can be used for FSW, each of which has advantages and challenges. State-of-the-art FSW employs various tool configurations, including the conventional, the stationary shoulder, and the dual-rotational configuration which is characterized by separate control of shoulder and probe. In this study, an innovative method to combine various tool configurations was developed by a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…On the other hand, considerable heat input, mechanical preparation, and severe occupational safety measures are necessary for TIG and MIG technologies [5]. Shoulder diameter (SD) and welding travel speed (TS), along with other parameters like rotation speed (Rs), tilt angle, and downward force, are also important to control the heat input for the welding material [6][7][8][9][10]. A review by Vaidyanathan et al [11] on the impact of the Shoulder Diameter to pin diameter (PD: SD) ratio on the joint strength of aluminum alloys reported that it compares one of the important parameters that govern tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, considerable heat input, mechanical preparation, and severe occupational safety measures are necessary for TIG and MIG technologies [5]. Shoulder diameter (SD) and welding travel speed (TS), along with other parameters like rotation speed (Rs), tilt angle, and downward force, are also important to control the heat input for the welding material [6][7][8][9][10]. A review by Vaidyanathan et al [11] on the impact of the Shoulder Diameter to pin diameter (PD: SD) ratio on the joint strength of aluminum alloys reported that it compares one of the important parameters that govern tensile strength.…”
Section: Introductionmentioning
confidence: 99%